Synthesis of stable fused furan-based molecule for organic electronics - Fun, Daryl Jia Wei (Nanyang Technological University, 2023)
The focus of this project is the chemical synthesis and characterization of a furan-based fused-ring unit. These units acts as cornerstone for development of non-fullerene acceptors for organic electronic applications. Organic chemical synthesis methodologies like esterification, Suzuki coupling, organolithium substituition, intramolecular Friedel-Crafts reaction and NBS bromination were carried out to acquire the target molecule DF6 (2,7-dibromo-4,4,9,9- tetrakis(4-octylphenyl)-4,9-dihydro-s-indaceno[1,2-b:5,6-b']difuran). All intermediates synthesized were identified with characterization techniques such as FTIR and H1-NMR spectroscopy. Suggestions to ameliorate the synthesis techniques will be discussed to aid potential future works revolving furan-based molecules.